Potential of marine sponge Jaspis sp.‐associated bacteria as an antimicrobial producer in Enggano Island - Sipriyadi Sipriyadi; Riziq Ilham Nurfahmi; Uci Cahlia; Risky Hadi Wibowo; Welly Darwis; Enny Nugraheni (Indonesian Journal of Biotechnology, 2022)
Sponges, a group of marine multicellular animals with a porous body structure, show potential for the production of bioactive compounds. Sponge‐associated bacteria are an alternative antimicrobial producer due to their high content of bioactive compounds. This study aimed to identify the highest‐potential antimicrobial‐producing bacteria isolate associated with Jaspis sp. sponges from Enggano island. The isolated bacteria were screened for antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Candida albicans using cultures, supernatants, pellets, and crude extracts. The study also conducted genetic identification to determine the identity of the isolate with the greatest potency and its closest relationship using the 16S rRNA gene. The antimicrobial activity was determined by monitoring and measuring the diameter of the formed clear zones. The results of the observations of morphological characteristics revealed nine isolates from Jaspis sp. that each consisting of 6 JABS isolates and 3 JABB isolates. Based on isolates that had antimicrobial activity, JABS6 isolates had the best antimicrobial activity, with the diameter of inhibition zones of 24.7, 8.2, 4.6, and 33.7 mm for E. coli, P. aeruginosa, S. aureus and C. albicans, respectively. The genome sequencing of the JABS6 isolate confirmed that it was identical to Bacillus thuringiensis strain USS‐CAP‐1. The study concludes that this finding shows promise for the further development of future antimicrobial agents.